Primal debt: a new concept in the field of womem reproductive rights (Revista de Investigaciones Universidad del Quindío, 2021)
In this paper it is proposed the concept of primal debt in the context of the women reproductive rights. Such a concept unfolds from the critical analysis of the symbiotic relationships between patriarchy and capitalism and the way in which they have historically been involved in perjury and economic exploitation of women through their natural reproductive capacity. In fact, it is an unquestionable biological aspect that women constitute the primary and unique source of continuous human capital generation; main productive factor since always used for the construction of all the material and immaterial wealth of human civilization, and its cumulative economic progress, expressed by the sum of the annual GDP of the nations. Therefore, even though women have achieved important recent achievements in the context of civil and labor rights, it is nevertheless imperative to recognize that there is an accumulated deity of millennia of injustice to women because of the unjustifiable current inexistence of the concept of primal debt, as well as its international recognition and consequent establishment as a topic of extreme social relevance to be developed in the context of the reproductive rights of women. Since, in this work, as a first action for the recognition of this primitive idea, it proposes the introduction of the concept of primal debt in the context of the reproductive rights of women; aiming at the future institution of its due monetary reimbursement, by means of effective legal mechanisms to be developed by the organizations responsible for the policies of defense of the rights of women on a world scale.
Keywords: human capital; human rights; reproductive rights; women's rights; patriarchy